Latent TGFβ-binding proteins 1 and 3 protect the larval zebrafish outflow tract from aneurysmal dilatation - Maryline Abrial; Sandeep Basu; Mengmeng Huang; Vincent Butty; Asya Schwertner; Spencer Jeffrey; Daniel Jordan; Caroline E. Burns; C. Geoffrey Burns (The Company of Biologists, 2022)
Aortic root aneurysm is a common cause of morbidity and mortality in Loeys-Dietz and Marfan syndromes, where perturbations in transforming growth factor beta (TGFβ) signaling play a causal or contributory role, respectively. Despite the advantages of cross-species disease modeling, animal models of aortic root aneurysm are largely restricted to genetically engineered mice. Here, we report that zebrafish devoid of the genes encoding latent-transforming growth factor beta-binding protein 1 and 3 (ltbp1 and ltbp3, respectively) develop rapid and severe aneurysm of the outflow tract (OFT), the aortic root equivalent. Similar to syndromic aneurysm tissue, the distended OFTs display evidence for paradoxical hyperactivated TGFβ signaling. RNA-sequencing revealed significant overlap between the molecular signatures of disease tissue from mutant zebrafish and a mouse model of Marfan syndrome. Moreover, chemical inhibition of TGFβ signaling in wild-type animals phenocopied mutants but chemical activation did not, demonstrating that TGFβ signaling is protective against aneurysm. Human relevance is supported by recent studies implicating genetic lesions in LTBP3 and, potentially, LTBP1 as heritable causes of aortic root aneurysm. Ultimately, our data demonstrate that zebrafish can now be leveraged to interrogate thoracic aneurysmal disease and identify novel lead compounds through small-molecule suppressor screens. This article has an associated First Person interview with the first author of the paper.